2002
DOI: 10.1124/jpet.301.3.945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tamoxifen on the Enzymatic Activity of Human Cytochrome CYP2B6

Abstract: Tamoxifen is primarily used in the treatment of breast cancer. It has been approved as a chemopreventive agent for individuals at high risk for this disease. Tamoxifen is metabolized to a number of different products by cytochrome P450 enzymes. The effect of tamoxifen on the enzymatic activity of bacterially expressed human cytochrome CYP2B6 in a reconstituted system has been investigated. The 7-ethoxy-4-(trifluoromethyl)coumarin O-deethylation activity of purified CYP2B6 was inactivated by tamoxifen in a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…The latter strongly inhibited CYP3A4 while also being metabolized by it. However, there are few reports about the inhibition of specific P450 isoenzymes by antitumor agents, eg, by thiotepa [42,43] , tamoxifen [44,45] and the less well-known sorafenib [46] . Our results showed that cytochrome P450 CYP3A4 did not metabolize C-1311 in cells, confirming our hypothesis that overexpression of this enzyme might modulate the cellular response of CHO cells following C-1311 treatment, even though CYP3A4 does not participate in metabolic transformations.…”
Section: Discussionmentioning
confidence: 99%
“…The latter strongly inhibited CYP3A4 while also being metabolized by it. However, there are few reports about the inhibition of specific P450 isoenzymes by antitumor agents, eg, by thiotepa [42,43] , tamoxifen [44,45] and the less well-known sorafenib [46] . Our results showed that cytochrome P450 CYP3A4 did not metabolize C-1311 in cells, confirming our hypothesis that overexpression of this enzyme might modulate the cellular response of CHO cells following C-1311 treatment, even though CYP3A4 does not participate in metabolic transformations.…”
Section: Discussionmentioning
confidence: 99%
“…SCH 66712 and EMTPP are structurally related with piperazine rings, substituted imidazoles, and fluorinated heteroaromatic rings. To our knowledge, there have been no reports of potent MBI of CYP2D6 and CYP3A4 by the same inactivator [though there are conflicting reports regarding inactivation by tamoxifen (Sridar et al, 2002;Zhao et al, 2002)]. Part of the lack of dual inactivators of both CYP3A4 and CYP2D6 is the difference in the presence of potential requisite nucleophile(s) in the active site.…”
Section: Discussionmentioning
confidence: 92%
“…However, in another independent study, Sridar et al (2002) mentioned that tamoxifen had no effect on the activities of CYP1B1.…”
Section: Discussionmentioning
confidence: 98%
“…Although the inhibitory activities of AIs against human CYP1B1 have not been previously studied, the effect of tamoxifen, a nonestradiol antiestrogen and a chemopreventive agent widely used for breast cancer treatment, was tested against human CYP1B1 as a possible inhibitor. However, the results of these studies were inconsistent (Rochat et al, 2001;Sridar et al, 2002). Rochat et al (2001) have reported that tamoxifen reversibly inhibits CYP1B1 and is a noncompetitive inhibitor.…”
Section: Discussionmentioning
confidence: 99%